Properties of traditional clay roof tiles manufacture in Kelantan, Peninsular Malaysia / Nor Hidayah Abdullah, Rodiah Zawawi and Zuraini Md Ali - Abdullah, Nor Hidayah; Zawawi, Rodiah; Md Ali, Zuraini (Faculty of Architecture, Planning & Surveying and UiTM Press, 2014)
The industry of traditional clay plain tiles, Singgora tiles, has been established in Kelantan for almost a century. However, the studies conducted in this field are insufficient. The purpose of this study is to test the properties of existing Singgora tiles to find out whether they satisfy the standard requirement. The tests of dimension measurement, surface quality, water absorption and flexural were done. The relative percentage constituent mineral and microstructure of Singgora tiles were measured by using XRD and SEM technique respectively. The physical test shows the length and thickness of Singgora tiles is not satisfied the standard. In addition, most of the samples have the defect on the surface and high water absorption. It is found that the strength of Singgora tiles is lower than the minimum requirement of standard. The presence of high percentage of quartz is observed in the mineral phase of Singgora tiles and the SEM analysis proved the incompletes vitrification among their microstructures.